In situ XANES and EXAFS Analysis of Redox Active Fe Center Ionic Liquids. (10th December 2015) - Apblett, Christopher A.; Stewart, David M.; Fryer, Robert T.; Sell, Julia C.; Pratt, Harry D. III; Anderson, Travis M.; Meulenberg, Robert W.
Abstract: In situ X-Ray Absorption Near Edge Spectroscopy (XANES) and Extended X-Ray Absorption Fine Structure (EXAFS) techniques are applied to a metal center ionic liquid undergoing oxidation and reduction in a three electrode spectroscopic cell. Determination of the extent of reduction under negative bias on the working electrode and the extent of oxidation are determined after pulse voltammetry to quiescence. While the ionic liquid undergoes full oxidation, it undergoes only partial reduction, likely due to transport issues on the timescale of the experiment. Nearest neighbor Fe-O distances in the fully oxidized state match well to expected values for similarly coordinated solids, but reduction does not result in an extension of the Fe-O bond length, as would be expected from comparisons to the solid phase. Instead, little change in bond length is observed. We suggest that this may be due to a more complex interaction between the monodentate ligands of the metal center anion and the surrounding charge cloud, rather than straightforward electrostatics between the metal center and the nearest neighbor grouping.